2009
DOI: 10.1111/j.1365-2559.2009.03361.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical and molecular genetic profiling of acquired cystic disease‐associated renal cell carcinoma

Abstract: Although the genetic profiles of ACD-associated RCC showed some similarity to those of papillary RCC, ACD-associated RCC distinctly revealed frequent gains on chromosomes 3 and Y. ACD-associated RCC is characterized not only by its particular clinical setting and histology, but also by its unique immunohistochemical and molecular genetic profiles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(37 citation statements)
references
References 22 publications
3
32
0
2
Order By: Relevance
“…The FISH reaction was performed as previously described. 19 FISH was performed with telomeric DNA probes for chromosome 19p (conjugated with Texas red) and chromosome 19q (conjugated with fluorescein isothiocyanate). FISH using centromeric probes for chromosome 7 (conjugated with Texas red) and chromosome 17 (conjugated with fluorescein isothiocyanate) was run in parallel.…”
Section: Fish Analysismentioning
confidence: 99%
“…The FISH reaction was performed as previously described. 19 FISH was performed with telomeric DNA probes for chromosome 19p (conjugated with Texas red) and chromosome 19q (conjugated with fluorescein isothiocyanate). FISH using centromeric probes for chromosome 7 (conjugated with Texas red) and chromosome 17 (conjugated with fluorescein isothiocyanate) was run in parallel.…”
Section: Fish Analysismentioning
confidence: 99%
“…In a few preliminary studies, calcium oxalate-associated RCC displays nonrandom chromosomal gains clustering on chromosomes 1, 2, 3, 6, 7, 16, 17, and Y. 22,23 This genetic profile is distinct from those of the types of RCC recognized in the current classification of renal cell neoplasms. In a study of 30 ACKD-associated RCCs, Sule et al found that 7 were of calcium oxalate type and 23 of other histologic types.…”
Section: Renal Neoplasms In Ackdmentioning
confidence: 97%
“…Une positivité pour le CD10, RCC et CD57 (RCC étant une glycoprotéine exprimé dans les cellules des tubes proximaux, CD57 étant un marqueur habituellement positif dans les adénomes métanéphriques) a été rapportée, néanmoins le diagnostic se fait sans profil immuno-histochimique spé-cifique. Des études cytogénétiques ont mis en évidence des gains de chromosome 7 et/ou 17, ainsi que des gains de Chr 3, et Y [10,11].…”
Section: Carcinome Rénal Associé à Une Maladie Rénale Kystique Acquiseunclassified